Analysis of the vibronic structure of the trans-stilbene fluorescence and excitation spectra: the S0 and S1 PES along the CeCe and Ce–Cph torsions. Issue 36 (7th September 2017) - Orlandi, Giorgio; Garavelli, Marco; Zerbetto, Francesco
Abstract : We analyze the highly resolved vibronic structure of the low energy (≤200 cm −1 ) region of the fluorescence and fluorescence excitation spectra of trans -stilbene in supersonic beams. Abstract : We analyze the highly resolved vibronic structure of the low energy (≤200 cm −1 ) region of the fluorescence and fluorescence excitation spectra of trans -stilbene in supersonic beams. In this spectral region the vibronic structure is associated mainly with vibrational levels of the Ce –Ce torsion ( τ ) and the au combination of the two Ce –Cph bond twisting ( ϕ ). We base this analysis on the well-established S0 ( τ, ϕ ) two-dimensional potential energy surface (PES) and on a newly refined S1 ( τ, ϕ ) PES. We obtain vibrational eigenvalues and eigenvectors of the anharmonic S0 ( τ, ϕ ) and S1 ( τ, ϕ ) PES using a numerical procedure based on the Meyer's flexible model [R. Meyer, J. Mol. Spectrosc., 1979, 76, 266]. Then we derive Franck–Condon factors and therefore intensities of the relevant vibronic bands for the S0 → S1 excitation and S1 → S0 fluorescence spectra. Furthermore, we assess the role of the bg combination of the two Ce –Cph bond twisting ( ν 48 ) in the structure of the S1 → S0 fluorescence spectra. By the use of these results we are able to assign most of the low energy vibrational levels of the S0 → S1 excitation spectra and of the fluorescence spectra of the emission from several low energy S1 vibronic levels. The good agreement between the observed and the computed vibrational structure of the S0 → S1 and S1 → S0 spectra suggests that the proposed picture of the E 1 ( τ, ϕ ) and E 0 ( τ, ϕ ) PES, in particular along the coordinate τ governing trans – cis photo-isomerization in S1, is accurate. In S0, the barriers for the Ce Ce torsion and for the au type Ce –Cph bond twisting are 16 080 cm −1 and 3125 cm −1, respectively, while in S1, where the bond orders of the Ce Ce and Ce –Cph bonds are reversed, the two barriers become 1350 cm −1 and 8780 cm −1, respectively.